PENGARUH MEDIA MASSA TERHADAP KEBANGKITAN POPULISME, SOLUSI ALTERNATIF, DAN RELEVANSINYA BAGI FENOMENA POPULISME DI INDONESIA - Mathias Jebaru Adon; Yasintus Harjon; Dionisius Sunardi (Program Studi Imu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Timor, 2022)
This study aims to discuss the influence of mass media on the rise of populism. Mass media is essentially a media that puts forward the truth in conveying information. The mass media is here to guide people to the true knowledge and truth about an event or occurrence. However, the reality that is happening in Indonesia is that the mass media often display conflicting information. The mass media often present information for the sake of meeting the interests of certain political groups and actors. As a result, the mass media has become a growing valley for populism in Indonesia. This study uses a literature study on the influence of mass media on the rise of populism. This study finds that the cause of the development of populism is because the mass media do not prioritize objectivity in conveying information and news. The solution offered by this research to minimize this is that the mass media need to return to their authenticity as a media that prioritizes truth and objectivity. In addition, the community needs critical reasoning in consuming various information and the importance of the government's control function in overseeing the ambiguity of news or information presented to the public.